COMPARISON STUDY OF ELEMENTARY SCHOOL SOCIAL STUDIES CURRICULUM IN SINGAPORE AND HONGKONG - Siska, Felia; Irwan, Irwan; Melia, Yenni; Meldawati, Meldawati; Febriani, Trina (PEDAGOGIK : JURNAL PENDIDIKAN, 2022)
This study aims to analyze the comparison of the primary school level school system in Singapore and Hong Kong, to analyze the comparison of the social studies curriculum at the elementary school level in Singapore and Hong Kong. The research method used is the library method with literature reviews from journals, books and other library sources. The results showed that; 1) The education systems in Singapore and Hong Kong have much in common. The school system starts at Kindergarten for 3 years, continues at the Primary or elementary school level. Then Secondary and College Level. The differences in the education systems of the two countries can be seen from the secondary or secondary school level; 2) The social studies education curriculum in Singapore and Hong Kong also has similarities as well as differences. The Social Studies curriculum at Elementary Schools in Singapore integrates the study areas of Geography, History, Economics and Sociology called Social Studies. Meanwhile, Hong Kong is included in the Personal, Social and Humanities Education group material as General Studies.